Provision of Resources in the Implementation of Tuberculosis-Multi Drugs Resistance Treatment Service in “X” Hospital - Dandy Nova Ardiansyah; Chriswardhani Suryawati; M Sakundarno Adi (Universitas Muhammadiyah Yogyakarta, 2019)
The purpose of the study is to evaluate the provision of resources in the implementation of Tuberculosis - Multi Drugs Resistance (MDR-TB) treatment service in “X” Hospital. The research type is qualitative research with in-depth interviews, observations, and documentation. The main informants are health workers who have been trained and involved in MDR-TB treatment service while the triangulation informants are MDR-TB patients and the Head of Community Health Center. Existing data is collected, reduced, presented, evaluated, drawn conclusion and verified with 5 components of resources studied, namely the components of labor, facilities, logistics, funding and work methods or procedures. In this study, information was obtained that the implementation of MDR-TB treatment service in “X” Hospital must be supported by adequate preparation of resources by following applicable regulations. Therefore, an appropriate and measurable planning mechanism is needed so that in the preparation of resource requirements namely personnel, funding, facilities and logistics, as well as working methods or procedures in MDR-TB treatment service, can be calculated accurately and measurably to develop service.